Conventional and non-conventional antigen-binding sites promote the development and function of chronic lymphocytic leukemia stereotyped subset #4 clones - Liu, Yun; Padhorny, Dzmitry; Catera, Rosa; Nicolo, Antonella; Yan, Xiao-Jie; Li, Stan Xiaogang; Iatrou, Anastasia; Mazzarello, Andrea N.; Destefani, Noemi; Allen, Steven L.; Kolitz, Jonathan E.; Rai, Kanti R.; et al. (Frontiers in Immunology, 2025)
Immunoglobulins (IGs) made by chronic lymphocytic leukemia (CLL) B cells are unique in that they bind themselves (homo-dimerize). This interaction leads to signal transduction with functional consequences that depend on the affinity of homo-dimerization. We have studied the antigen-binding properties of the IGs from a subset of patients with CLL (Subset #4) that homo-dimerize at high affinity. Previously, we had found that subset #4 IGs bound viable lymphocytes. Our new studies, probing an array of >8,000 antigens, indicate that these IGs also bind influenza virus. Because of the IGs high-affinity homo-dimerization, we asked if the defined foreign- and self-antigenic interactions were mediated by conventional B-cell receptor (BCR) domains or a non-conventional receptor created by homo-dimerization. The studies indicated the latter since abrogation of homo-dimerization eliminated binding to influenza virus and its hemagglutinin and to viable lymphocytes. Using these findings, we modeled a developmental path whereby a naive IgM+ B cell with subset #4 heavy and light chain variable domains used the conventional BCR to interact with auto- and foreign antigens and acquire homo-dimerization capacity to create the non-conventional antigen-receptor when transitioning to a leukemic cell. Future studies will determine if this process is an idiosyncratic occurrence or a physiologic principle.